2019
DOI: 10.1155/2019/7436592
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Practices of Project Governance in Public Sector Infrastructure Program in Pakistan

Abstract: The governance of public sector infrastructure projects became an important area of interest in the literature on project management. Today, it is a focal point for policymakers to ensure successful appraisal and implementation of government-sponsored programs. This paper aims to investigate the current practices of project governance (PG) for steering the public sector infrastructure program in Pakistan. An empirical investigation was carried out among professionals of public sector organizations involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Contextual research findings suggest that organizations, corporations and portfolios invest in settings that perceive better political stability with an above-average return (Chepkoech and Rotich, 2017;Shakhov and Piterska, 2018). It is very rational and logical that individuals and organizations avoid investing in locations where their physical and financial safety and security are threatened (Embrechts et al, 2003;Khan et al, 2018). High levels of crime, terrorism, nationalization of property, armed conflicts, foreign invasion and corruption add to investment uncertainty and the perception of PR (Hassan et al, 2017;Islam et al, 2018;Millhollan and Kaarst-Brown, 2016).…”
Section: Political Risk (Pr)mentioning
confidence: 99%
See 1 more Smart Citation
“…Contextual research findings suggest that organizations, corporations and portfolios invest in settings that perceive better political stability with an above-average return (Chepkoech and Rotich, 2017;Shakhov and Piterska, 2018). It is very rational and logical that individuals and organizations avoid investing in locations where their physical and financial safety and security are threatened (Embrechts et al, 2003;Khan et al, 2018). High levels of crime, terrorism, nationalization of property, armed conflicts, foreign invasion and corruption add to investment uncertainty and the perception of PR (Hassan et al, 2017;Islam et al, 2018;Millhollan and Kaarst-Brown, 2016).…”
Section: Political Risk (Pr)mentioning
confidence: 99%
“…The PC is based on mutual respect, beliefs, perceptions and informal obligations among employees and employers (Khan et al, 2018;Rani et al, 2018). It involves principles and transactional long-term social exchange and development among employees and employers (Kalkman and de Waard, 2017).…”
Section: The Psychological Contract (Pc)mentioning
confidence: 99%
“…Objectives of public projects should be aligned with policies, and the top-down policy implementation affects the effectiveness of the project governance system [59,60]. As public projects are policy implementation tools for accomplishing government's programs, linking policies is the key governance practice in this kind of projects that needs to be followed [61].…”
Section: Analysis Of Cocitation Clustersmentioning
confidence: 99%
“…In this regard, public sector project management is gradually becoming an imperative subject due to the demands for improvement in accountability and organizational effectiveness in government organizations. Despite the economic significance of infrastructure projects in developing countries, it has been generally observed that government officials are not well equipped with contemporary project management skills deemed necessary for attaining the desired outcomes (Khan et al, 2019a). In such countries, these high valued projects have to deal with issues that are distinctive to multiple layers of overdemanding stakeholders, weak procurement systems, and administrative approvals (Ahsan and Gunawan, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, scholars have addressed the issues in the performance of the public sector infrastructure of Pakistan (Gazder and Khan, 2018;Irfan and Hassan, 2017;Khan et al, 2019a;Khan et al, 2021a;Khan et al, 2021b;Khattak et al, 2016). The review of the aforementioned studies shows that the researchers have not addressed the theme of external SM in public sector infrastructure projects of Pakistan.…”
Section: Introductionmentioning
confidence: 99%